PERHITUNGAN BIAYA TAMBAHAN DENGAN METODE ACCRUED BENEFIT COST PADA PENDANAAN PROGRAM PENSIUN MANFAAT PASTI - Siti Nurlatifah; Sudarno Sudarno; Abdul Hoyyi (Jurnal Gaussian, 2015)
Supplemental costs in funding pension plan is a cost to be issued by the employer to the pension fund in case shortage of funds (deficit) in the funding of defined benefit plans. There are several methods can be used, one of them is accrued benefit cost method. This research explained about the calculation of the supplemental costs on defined benefit plans with a case study on BMKG Semarang. The data used 34 BMKG employee salaries who had not attained 50 years old in 2015. The calculation is done by concern the beginning of an employee salary, interest rate, period of employment, and increase of salary rate. Supplemental costs that must be issued by BMKG in 2015 is Rp. 81.748.084. That cost can sufficient the pension benefits that will be received by the employee if the funding was deficit. If the funding pension had a surplus, that cost can be used as an investment company. Keywords: supplemental cost, defined benefit plans, accrued benefit cost.